Effectiveness of Intervention Programs Addressing Work-Family Conflict Among Working Mothers: A Systematic Review - Kaulina, Farah; Permatasari, Henny (Jurnal Kesehatan, 2025)
Work-family Conflict (WFC) is a significant issue for working mothers, affecting their well-being and family dynamics. This review aims to evaluate the effectiveness of various interventions to reduce WFC. This study using a systematic review was conducted with the PICO framework. Studies were selected based on criteria including working mothers with children (infancy to school age), full-text availability, English language, and publications from 2014 to 2024. The risk of bias was assessed using the JBI Critical Appraisal Tools, and the results were synthesized through a narrative synthesis. Out of 258 articles screened, 5 studies met the inclusion criteria. The review found that interventions such as Rational Emotive Behavior Therapy (REBT), time management training, multimedia education, resilience training, stress management, and self-reflection effectively reduced work-family conflict (WFC), thereby improving both mental health and work-family balance. The main limitation of this review is the small number of included studies and variability in methodologies. Future research should focus on integrating diverse interventions and exploring long-term effects. The findings highlight the role of Occupational Health Nurses (OHNs) in supporting working mothers in managing work-family conflict (WFC).